Application of by Product of a Steel (Steel Slag) As Fractional Additional of Mixture Coarse Aggregate in Concrete - Safdar, Muhammad Ali; Mohammad, Mehran; Ahmad, Sohail; Ali Shah, Syed Waqar (Advances in Social Sciences Research Journal, 2019)
As we already know that human’s population are increasing day by day and in order to meet their various transportation-al and housing needs construction is going on at a very faster rate and there might be a chance that usage of natural coarse aggregate become less because natural mountains are being damaged due to drilling or by blasting. In this investigation an attempt is being made to find a solution in which original strength and durability can be obtained by usage of by-product of steel (Steel Slag). The purpose of this investigation is to examine analytically, the “APPLICATION OF STEEL SLAG AS FRACTIONAL ADDITIONAL OF COARSE AGGREGATES” examined by replacement of natural coarse aggregates by different ratio of steel slag at 20,40,60,80 and 100 % by using the mix design of class A concrete and its strength was more than 4500 psi .The specimen standard cylinders size and beams (8 inch,8 inch and 21 inch ) size were used and they were tested at 7,14 and 28 days interval .It was properly water cured .Various concrete tests were being performed ,In order to find out the actual behaviour of concrete and the tests were compressive, split, flexural and slump test. The test graph shows that there is a wide variation in compressive, split, flexural and slump strength of natural coarse aggregate replaced by steel slag for 7,14 and 28 days.